SFS? Not likely. (August 2013) - Koenderink, Jan; van Doorn, Andrea; Wagemans, Johan
SFS (Shape From Shading) theory is based upon the Lambertian paradigm. Our visual demonstrations imply that this paradigm fails to apply to the conventional stimuli used to probe vision.